Los orígenes de la psicología - León Donayre, Ramón (2016)
The origins of psychology, the philosophical schools, her relationships with the arts and the social sciences, and her crisis are briefly presented in this communication. Scientific psychology is not raised as a isolated science, but she has a large developmental process, which was influenced by the social changes.